2005
DOI: 10.1021/jf047944i
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental Stresses on Stability of O/W Emulsions Containing Cationic Droplets Stabilized by SDS−Fish Gelatin Membranes

Abstract: Oil-in-water (O/W) emulsions containing small oil droplets (d32 approximately 0.22 microm) stabilized by sodium dodecyl sulfate (SDS)-fish gelatin (FG) membranes were produced by an electrostatic deposition technique. A primary emulsion containing anionic SDS-coated droplets (zeta approximately -40 mV) was prepared by homogenizing oil and emulsifier solution using a high-pressure valve homogenizer (20 wt % corn oil, 0.46 wt % SDS, 100 mM acetic acid, pH 3.0). A secondary emulsion containing cationic SDS-FG-coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 36 publications
3
53
1
Order By: Relevance
“…Hence, TPGS mixed emulsifiers can mediate higher Gen-loading capacity and improved drug retention in comparison with single-component emulsifiers, without producing a substantial change of NE ζ-potential, at the final fixed pH of 5.7. In complete agreement with previous data, 27,40 for Chito-layered micro/nanoscale emulsions, the particle electrical charges were found to be inversely dependent on the final adjusted pH value. As pH increased, the cationic charge decreased until neutral or slightly anionic (≈-7.5 mV, at pH 7.0).…”
supporting
confidence: 91%
“…Hence, TPGS mixed emulsifiers can mediate higher Gen-loading capacity and improved drug retention in comparison with single-component emulsifiers, without producing a substantial change of NE ζ-potential, at the final fixed pH of 5.7. In complete agreement with previous data, 27,40 for Chito-layered micro/nanoscale emulsions, the particle electrical charges were found to be inversely dependent on the final adjusted pH value. As pH increased, the cationic charge decreased until neutral or slightly anionic (≈-7.5 mV, at pH 7.0).…”
supporting
confidence: 91%
“…On the other hand, lower ash contents (~1.5%) were observed in fresh fish, hence corroborating the influence of the ingredients on the ash content (SURH et al, 2005). Table 2 shows that the experiments that presented lower protein contents led to higher ash contents in the fish nugget (experiments 6, 8, and 10).…”
Section: Microbiological Analysissupporting
confidence: 68%
“…In some experiments, sodium dodecyl sulfate (SDS) with relatively high hydrophilic-lipophilic balance (HLB = 40) has also been used as a model anionic surfactant. SDS is a non-food-grade emulsifier, but it does represent a number of small-molecule anionic surfactants that are commonly used in foods, can be obtained in high purity and its properties are generally well understood [Stauffer, 2001;Surh et al, 2005;Thanasukarn et al, 2006]. It has been found that surfactant-coated droplets remain highly negative across a wide pH range [Hong & McClements, 2007].…”
Section: Characteristics Of Multilayered Membrane Componentsmentioning
confidence: 99%
“…in commercial oil the iron and copper concentration has been recommended to be < 0.1 ppm and < 0.2 ppm, respectively [Katsuda et al, 2008]. However, it has to be stressed, that the magnitude and range of electrostatic interactions between charged interfacial membranes and transition metals can be reduced as the ionic strength of the solution increases because of the accumulation of counter-ions around the surfaces, which is usually referred to as electrostatic screening [Surh et al, 2005;Guzey & McClements, 2006;Zeeb et al, 2011].…”
Section: Major Lipophilic Bioactive Food Components Propertiesmentioning
confidence: 99%